IL3 SNP rs40401 variant is a risk factor for rhinoconjunctivitis in Japanese women: The Kyushu Okinawa Maternal and Child Health Study - Miyake, Yoshihiro; Tanaka, Keiko; Arakawa, Masashi (Cytokine (Philadelphia, Pa.), 2013)
•IL3 SNP rs40401 variant was significantly positively associated with rhinoconjunctivitis.•No interaction was found between the SNP and smoking affecting rhinoconjunctivitis.•Also, there was no significant interaction between the SNP and older siblings. No studies have investigated the relationship between IL3 single nucleotide polymorphism (SNP) rs40401 and allergic rhinitis. We performed a case-control study to examine this issue and to assess interactions between the SNP and smoking or older siblings in young adult Japanese women. Included were 393 women who met the criteria of the International Study of Asthma and Allergies in Childhood (ISAAC) for rhinoconjunctivitis. Controls were 767 women without rhinoconjunctivitis according to the ISAAC criteria who had not been diagnosed with allergic rhinitis by a doctor. Compared with women with the TT genotype of SNP rs40401, those with the CC genotype had a significantly increased risk of rhinoconjunctivitis: the adjusted OR was 1.52 (95% CI: 1.05-2.19). This positive relationship was significant under the additive model: the adjusted OR was 1.23 (95% CI: 1.02-1.47). The positive association fell just short of the significance level under the dominant or recessive model. There was no significant interaction between SNP rs40401 and smoking with respect to rhinoconjunctivitis. Compared with subjects with the TT or TC genotype of IL3 SNP rs40401 who had one or more older siblings, those with the CC genotype who had no older siblings had a 2.33-fold increased risk of rhinoconjunctivitis; nevertheless, the interaction was not significant. This is the first study to show a significant positive association between IL3 SNP rs40401 variant and the risk of rhinoconjunctivitis. We could not find evidence for interactions between SNP rs40401 and smoking or older siblings affecting rhinoconjunctivitis.